CONTROL OF AGGRESSIVE BEHAVIOR AND LEVEL OF AGGRESSION AMONG ADOLESCENTS IN HIGH SCHOOL - Graczyk, M.; Skalski, D. W.; Kowalski, D.; Kindzer , B.; Grygus, I. M. (Rehabilitation and Recreation, 2022)
Aggression nowadays is a phenomenon so common that each of us encounters it in our daily lives.Whether at home or on the street, in the park or at school, aggression is spreading its circles more and moreintensively both among adults and among children and adolescents. Increasingly, we witness brutal behav-ior, we hear constant curses, and vulgar insults become «daily bread» for people. Aggression and violenceare phenomena that are receiving more and more attention, both in scientific works and in the mass media.Not a day goes by that we don’t read in the newspaper or hear about the act of violence on TV. This hasto do with the enormity of the scale and drastic nature of this phenomenon. Aggression and violence areone of the more worrying problems. For obvious reasons, this phenomenon is of great public concern.The number of young people who become aggressive is constantly increasing, and victims of violence areeven more often heard. The present times have led to the fact that violence becomes a means of reachingthe intended ends. Only victims and people at risk of aggression are aware of the problem of aggression.The scale of the phenomenon of aggression is constantly increasing, and the number of offenses commit-ted by students is sounding the alarm. In the Polish school, the problem of violence is becoming moreand more serious. There are frequent cases of aggression not only among students, but also in relation toteachers. In schools, there is a growing sense of helplessness in the face of aggression and violence. Theprinciple of cooperation and mutual assistance has been replaced by the principles of domination, extortionand force. Provocative behavior of students, motor hyperactivity, inability to concentrate and unwilling-ness to acquire knowledge make teaching extremely difficult. Increasingly, there are cases of ignoringthe teacher’s commands, ridiculing adults, vandalism. Students play a kind of fight with teachers, as well aswith their colleagues. Communication based on gaining advantage and forcing submission is created. Theschool corridor has become an arena of undesirable behavior. Verbal violence: profanity, swearing, insultscome from both boys and girls. Very often physical violence is observed – taking objects, fights, pushing.A common occurrence is the exploitation of younger pupils by older yearbooks. Currently, numerousresults of scientific research indicate the causes of aggression in three areas: genetic, biochemical and envi-ronmental. A large group of researchers practically all over the world is currently conducting research that could be described as a search for the aggression gene. In the course of this research, in the late sixtiesof our century, scientists came up with an interesting clue, which was supposed to be an additional Y chro-mosome, the presence of which was detected in 3 % of men staying in prison psychiatric hospitals. Becausethis frequency was well above the average in society as a whole, the double Y chromosome was consideredby some scientists to be a sign of an aggressive personality. The situation changed when a broader studyproved that most of its carriers are calm people who do not show any particularly aggressive tendencies.Research is still being carried out to determine the influence of genes on the level of aggression, and per-haps recent research and successes of scientists in understanding human DNA will bring more preciseresults in this area.